Adsorption and photocatalytic properties of NiO nanoparticles synthesized via a thermal decomposition process. Issue 5 (14th March 2018) - Ramesh, Martha; Rao, Martha Purna Chander; Anandan, Sambandam; Nagaraja, Hosakoppa
Abstract: Abstract : NiO nanoparticles (NPs) were synthesized at different annealing temperatures via a thermal decomposition process and characterized using X-ray diffraction, scanning electron microscopy, and UV-vis spectroscopy. The NiO NPs prepared at higher annealing temperature (400 °C) were shown excellent adsorption and photocatalytic activity toward textile dyes reactive black 5 (RB-5) and methylene blue (MB). About 87.2% of RB-5 in 60 min and 70.2% of MB in 5 h was removed using NiO NPs synthesized at 400 °C. The photocatalytic degradation of MB was found to increase with an increase in the annealing temperature of the catalyst. Moreover, the kinetic study revealed that the adsorption and photocatalytic activity of NiO NPs followed the second and first-order kinetics, respectively. The enhanced performance of NiO NPs toward dye removal might be related to its optical and structural properties.